Skilled Labor Flows : Lessons from the European Union - Kahanec, Martin (World Bank, Washington, DC, 2013)
This study evaluates European Union (EU) experience of the mobility of skilled labor migrants after the 2004 and 2007 EU enlargements and from the European Neighborhood Policy (ENP) countries. The study concludes that migration generally improves the allocated efficiency of labor markets and there is little if any evidence of statistically significant or economically relevant negative aggregate effects of migration on receiving labor markets. While outflow of young and skilled workers may pose risks to sending countries' economic prospects and public finance, circular migration, brain gain, and remittances attenuate such risks, and have the potential to become powerful engines of convergence. Obstructive legislation and ill-designed migration policies impede migration and deprive sending and receiving of such potential benefits.